Chicken soup for the soul : the cat did what? : 101 amazing stories of magical moments, miracles and -- mischief - Newmark, Amy; Lambert, Miranda, 1983- (Chicken Soup for the Soul Pub., LLC, 2014)
Collects 101 stories about the absurdities, mischief, miracles, and magic that cats bring to our lives.